A clinico-surgical outcome of vaginal hysterectomy with or without hydro dissection: a Quasi experimental study - Hurakadli, Kirti M.; Pujari, L. L.; G., Prashant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Vaginal hysterectomy -the signature operation of gynecologic profession, is a hallmark of gynecological extirpative hysterectomy surgery and surgical excellance1. In the era of minimal invasive surgery, Nondescent vaginal hysterectomy has evolved over the years and is opted over abdominal route. It is because of lower morbidity, less postoperative pain, more rapid return to normal activities and lesser hospital stay associated with this route of surgery. Practice of hydrodissection with diluted adrenalin has been noticed by few surgeons. Methods: We did a retrospective analysis of 267 cases of vaginal hysterectomies in our hospital over a period of three years, regarding the benefit of hydro dissection in reducing the blood loss and time of surgery, so as to incorporate this technique on routine basis. Results: Of 267 cases, NDVH was done in 107 (40.1%) cases, and 160 (59.9%) patients underwent vaginal hysterectomy with PFR. Of 267 cases, 121 (45.3%) cases had hydro dissection. In 146 (54.7%) cases hydro dissection was not done. The mean blood loss was significantly reduced in cases with hydro dissection to a mean of 1.07 mops when compared to cases with no hydro dissection-mean of 1.71 mops. Duration of surgery was also significantly reduced to a mean of 39.9 minutes in cases with hydro dissection when compared to cases with no hydro dissection with a mean of 46.3 minutes. There was no significant change in duration of hospital stay. Conclusions: Hydro dissection with diluted adrenaline should be routinely practice by all vaginal surgeons to reduce the duration of surgery and intraoperative blood loss.